Geological history of the Dnipro Rapids from Paleogene to Holocene - Manyuk Volodymyr (Днепропетровский национальный университет им. Олеся Гончара, 2019)
During its long history, the rapids section of the large river the Dnipro not only posed a problem for navigation, but also attracted people with its picturesque rocky landscapes unusual for the Steppe Prydniprovie. Nobody who had saw their beauty was left indifferent. History has preserved lots of recorded impressions from various visits to the Rapids from the Ancient Greek philosphers to exceptional works of Dmitro Yavornytsky. However, the geological studies were fragmented and there is no integrated source focussing on the geological structure of the Dnipro Rapids. We analyzed the results of the explorations of Valerian Domger, a famous researcher of the geology of Middle Prydniprovie.His routes investigated almost every corner of the then Katerynoslav governorate. After the creation of the Prydriprovie Regional Landscape Park (PRLP) in 2008 within the territory of part of the Dnipro Rapids, a question of restoration of its geological history should have emerged, but that has not happened. The year 2017 became the year of rebirth of the PRLP and recognition of geological component as the key feature of its restoration. The Pre-Cambrian stage of the geological history of the Naddniprovia Rapids is described in the author`s publication in early 2018, which focused on the most ancient history of the Rapids. The Phanerozoic Eon is analyzed in this work and focuses on the lithogical-facial peculiarities of the sedimentary rocks from Paleogene to Quaternary rocks on the basis of stratigraphic and paleontological data, according to which they have beendivided in detail. We determined the patterns in the structure of Quaternary deposits, the correlation of subaerial and subaquaticformations of different genetic types was made according to the use of the climatic-stratigraphic or paleoclimatic principle of division. The possibilities of creating a geological park on the basis of the“Dnipro Rapids” Regional Landscape Park ( "Dniprovi Porohy' RLP )areexplored and substantiated.
Keywords: Dnipro Rapids; regional landscape park; geology; Paleogene Period; Neogene Period; Quaternary deposits; Дніпрові пороги; регіональний ландшафтний парк; геологія; палеоген; неоген; четвертинні відклади; Cenozoic::Paleogene; Кайнозой::Палеоген; Кайнозой::Неоген; Cenozoic::Quaternary; Cenozoic::Neogene